Block of AMPA Receptor Desensitization by a Point Mutation outside the Ligand-Binding Domain - Yelshansky, Maria V. (J Neurosci, 2004)
Desensitization of ionotropic glutamate receptors (GluRs), specifically the AMPA receptor subtype, shapes the postsynaptic response at certain synapses in the brain. All known mechanisms that alter desensitization, either pharmacological or mutational, are associated with the ligand-binding domain. Here we report that substitution of a conserved positively charged arginine (R) with a negatively charged glutamate in the linker between the pore-forming M3 segment and the S2 lobe, a region outside the ligand-binding domain, blocks desensitization in homomeric AMPA receptors composed of GluR-B(i) subunits. A charge-reversing substitution of a glutamate adjacent to this conserved R enhanced desensitization, consistent with these effects attributable to electrostatics. Homologous substitutions of the conserved R in GluR-B(o), GluR-A(i) and the kainate receptor GluR-6 subunits produced comparable but less visible effects on desensitization. Subunit specificity was also apparent for accessibility of substituted cysteines in the M3–S2 linker, suggesting that this part of the channel is not structurally identical in different GluRs. Additionally, reactivity with a sulfhydryl-specific reagent was state dependent, suggesting that the conformations of the nonconducting closed and desensitized states are different at the level of the M3–S2 linker. Our results therefore represent the first identification of elements outside the ligand-binding domain affecting desensitization in non-NMDA receptor channels and suggest that electrostatic interactions involving charged residues in the M3–S2 linker influence channel gating in a subunit- and subtype-specific manner.